DOI: 10.11606/d.64.2017.tde-18102017-082750
|View full text |Cite
|
Sign up to set email alerts
|

Análise genômica e funcional da Nodularia spumigena CENA596 formadora de florações em tanques de produção de camarões

Abstract: POPIN, R. P. Genomic and functional analysis of the bloom-forming Nodularia spumigena CENA596 in shrimp production ponds. 2017. 84 p. Dissertação (Mestrado)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 94 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…The concentration of nodularin recorded in the stationary phase of our experiment (1.3-6.0 µg L −1 ) was relatively low, considering that values of 0.8-220 µg L −1 (Heresztyn and Nicholson, 1997;McGregor et al, 2012) and greater than 15,000 µg L −1 (Mazur and Pliński, 2003) had previously been found in the environment. It must be noted that the ELISA method used in our study does not detect the nodularin variants, such as NOD-R and [D-Asp'] NOD, which can be produced by our strain (Popin, 2017). Thus, the nodularin concentration found in this study is possibly underestimated.…”
Section: Nodularin Productionmentioning
confidence: 67%
See 2 more Smart Citations
“…The concentration of nodularin recorded in the stationary phase of our experiment (1.3-6.0 µg L −1 ) was relatively low, considering that values of 0.8-220 µg L −1 (Heresztyn and Nicholson, 1997;McGregor et al, 2012) and greater than 15,000 µg L −1 (Mazur and Pliński, 2003) had previously been found in the environment. It must be noted that the ELISA method used in our study does not detect the nodularin variants, such as NOD-R and [D-Asp'] NOD, which can be produced by our strain (Popin, 2017). Thus, the nodularin concentration found in this study is possibly underestimated.…”
Section: Nodularin Productionmentioning
confidence: 67%
“…However, the optimal environmental conditions for the Brazilian strain and how they compare to strains from other sites in the world are not yet known. Phylogenetic analyses based on its 16S rRNA gene indicated that the Brazilian strain is closely related to the strains from Australia (Popin, 2017;Silveira et al, 2017). Alternatively, based on the analysis of genome, 31 proteins of this same Brazilian strain were grouped with the Baltic Sea strain (Popin, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation